Mitral valve replacement in the presence of severe pulmonary hypertension. Issue 3 (June 1976) - Kaul, T K; Bain, W H; Jones, J V; Lorimer, A R; Thomson, R M; Turner, M A; Escarous, A
Abstract : Thirty patients with severe preoperative pulmonary hypertension (pulmonary artery pressure range 90-165 mmHg, mean 118 mmHg) were reviewed following single mitral valve replacement, with prosthetic valves, within the last 10 years (1964-74). The early and late mortality for this group was no different from that of the total series of mitral valve replacements performed over the same period. Marked postoperative clinical improvement was accompanied by corresponding radiological and electrocardiographic changes. In addition there was a statistically highly significant haemodynamic improvement in the 21 survivors (mean survival time 5 1/2 years). At recatheterization the mean pulmonary artery pressure was 41-5%, the mean wedge pressure 46-3%, and the transpulmonary gradient (PAm-LAm) 36-1% of the preoperative values. It is concluded that gross pulmonary hypertension is not per se a contraindication to mitral valve replacement surgery.